Tirakat Akademik sebagai Lived Religion Santri Pesantren Modern - Salma Rutbati Aliyyah; Muh. Hanif (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aims to analyze academic tirakat practices as a manifestation of lived religion among santri in modern pesantren. Using a qualitative phenomenological approach, the research was conducted at Pesantren Modern Darul Qur'an Al Karim. Data were collected through participant observation and in-depth interviews with santri, pesantren caregivers, teachers, and parents. The findings reveal that academic tirakat is practiced through voluntary fasting, night prayers, wirid recitation, sleep reduction, and limitation of gadget use. These practices are understood by santri as spiritual efforts supporting academic achievement and Qur’anic memorization. The pesantren leadership also interprets educational success as a combination of intellectual effort and spiritual endeavor. Furthermore, academic tirakat contributes to psychological well-being, learning motivation, and resilience in facing academic pressure. This study concludes that academic tirakat represents a living manifestation of religion within pesantren educational culture and demonstrates the integration of spirituality and intellectual development in modern Islamic education.